Computed tomography-guided radiofrequency ablation of intra-articular osteoid osteoma: a single centre's experience. (18th August 2017) - Filippiadis, D. K.; Velonakis, G.; Kostantos, C.; Kouloulias, V.; Brountzos, E.; Kelekis, N.; Kelekis, A.
Abstract: Objective: To evaluate safety and efficacy of radiofrequency ablation (RFA) in the treatment of painful intra-articular osteoid osteoma. Materials and methods: During the last 3 years, 15 patients underwent computed tomography (CT)-guided biopsy and RFA of symptomatic intra-articular osteoid osteoma. In order to assess and sample the nidus, a coaxial bone biopsy system was used. Biopsy was performed and followed by ablation session with osteoid osteoma protocol in all cases. Procedure time (i.e. drilling including local anaesthesia and ablation), amount of scans, the results of biopsy and pain reduction during follow-up period are reported. Results: Access to the nidus through normal bone, biopsy and electrode insertion was technically feasible in all cases. Median procedure time was 54 min. Histologic verification of osteoid osteoma was performed in all cases. Median amount CT scans, performed to control correct positioning of the drill and precise electrode placement within the nidus was 9. There were no complications or material failure reported in our study. There was no need for protective techniques of the articular cartilage. Pain reduction was significant from the first morning post ablation and complete at the one week and during the follow-up period. No recurrences were noted. Conclusions: RFA under CT guidance is a safe and efficient technique for the treatment of painful intra-articular osteoid osteoma. Imaging guidance, extra-articular access through normal bone and exact positioning of the needle-electrode inside the nidus facilitate safety of the technique and prevention of damage to the articular cartilage.